2017
DOI: 10.1037/xhp0000410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the sources and functions of gradiency in phoneme categorization: An individual differences approach.

Abstract: During spoken language comprehension listeners transform continuous acoustic cues into categories (e.g. /b/ and /p/). While longstanding research suggests that phonetic categories are activated in a gradient way, there are also clear individual differences in that more gradient categorization has been linked to various communication impairments like dyslexia and specific language impairments (Joanisse, Manis, Keating, & Seidenberg, 2000; López-Zamora, Luque, Álvarez, & Cobos, 2012; Serniclaes, Van Heghe, Moust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
188
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(211 citation statements)
references
References 81 publications
20
188
3
Order By: Relevance
“…Languages differ both in which cues are relevant and the relative importance of these cues (e.g., cross‐linguistic differences in the phonetic realization of the stop voicing contrast: Lisker & Abramson, ), and dialectal variation can often be ascribed to differences in cue weighting (e.g., use of VOT vs. f0 in the Korean stop contrast: Y. Kang, Schertz, & Han, ; Lee, Politzer‐Ahles, & Jongman ()). Even within a homogeneous language group, individual cue‐weighting strategies differ (e.g., Kapnoula, Winn, Kong, Edwards, & McMurray, ; Schertz, Cho, Lotto, & Warner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Languages differ both in which cues are relevant and the relative importance of these cues (e.g., cross‐linguistic differences in the phonetic realization of the stop voicing contrast: Lisker & Abramson, ), and dialectal variation can often be ascribed to differences in cue weighting (e.g., use of VOT vs. f0 in the Korean stop contrast: Y. Kang, Schertz, & Han, ; Lee, Politzer‐Ahles, & Jongman ()). Even within a homogeneous language group, individual cue‐weighting strategies differ (e.g., Kapnoula, Winn, Kong, Edwards, & McMurray, ; Schertz, Cho, Lotto, & Warner, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that individuals may vary in their use of secondary cues in perception (see Schertz & Claire, 2019 for a review of individual variability in cue weights). Some individuals use a secondary cue more than others for F0 in English stop voicing (Kapnoula, Winn, Kong, Edwards, & McMurray, 2017;Kong & Edwards, 2016;Shultz, Francis, & Llanos, 2012) and vowel duration for English tense/lax vowels (Kim & Clayards, 2019). A common method to quantify individual cue weights is to use regression coefficients fit to each individual's responses (e.g., Shultz et al, 2012), or to use by-individual deviations from the population coefficient for a single regression model fit to all data ('random slopes,' e.g., Clayards, 2018; see also Schertz & Claire, 2019 for discussion of different methods).…”
Section: Multiple Cues: Individual Variability and Sound Changementioning
confidence: 99%
“…Some researchers have argued that more use of a secondary cue is associated with more gradient sensitivity to primary cues, using a visual analog scaling task rather than a categorical decision task (Kapnoula et al, 2017;Kong & Edwards, 2016). Thus, the positive correlations in Clayards (2018) and the relationship between gradient sensitivity and cue use (Kapnoula et al, 2017;Kong & Edwards, 2016) both point to some listeners' speech perception being more closely tied to the acoustics of the stimulus than others. However, as noted above, not all studies have found this relationship.…”
Section: Multiple Cues: Individual Variability and Sound Changementioning
confidence: 99%
“…Some recent work has begun to probe the extent to which individual differences in categorization strategies can be linked to other aspects of speech perception and/or general cognitive abilities. For example, Kapnoula et al (2017) found that individuals who show more gradient categorization of the English stop voicing contrast (i.e., a shallower slope on a VOT categorization curve) also show greater use of f0 (a secondary cue) and propose several potential reasons for this correlation. Clayards (2018b) showed that individuals who exhibited higher cue weights for a given dimension in a given contrast also tended to show higher cue weights on a different dimension on a different contrast, suggesting that some individuals may simply show more consistent labeling patterns than others (see also Hazan and Boulakia, 1991).…”
Section: Stability Of Individual Cue Use Across Languages In Bilingualsmentioning
confidence: 99%